2007
DOI: 10.1016/j.domaniend.2006.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of aquaporin-9 (AQP9) in porcine hepatic tissue and hepatocytes in monolayer culture

Abstract: Aquaporins (AQPs) are members of a large family of integral membrane proteins involved in the rapid movement of water and neutral solutes across cell membranes. In this study, we have prepared an affinity-purified porcine-specific polyclonal antiserum to AQP9 and have investigated the distribution and expression of AQP9 in pig liver tissue and in hepatocytes in primary culture. Immunocytochemical analysis showed that AQP9 was primarily localized in the membrane structures of hepatocytes and was not associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…This idea agrees with the functional and regulatory distinctions known to exist between AQP8 and AQP9 in rat liver (Garcia et al 2001, Kuriyama et al 2002. The absence of T3 regulation of AQP9 in rat liver does not confirm the increase in the mRNA levels of AQP9 seen by Caperna et al (2007) who looked at the expression and distribution of AQP9 in pig liver tissues after stimulation with hormones, such as glucagon, insulin, and T3. Because the T3-induced enhancement of AQP9 transcript seen by Caperna et al (2007) was not accompanied by a parallel increase in the same AQP at a protein level, it is conceivable to speculate that the T3 modulation of AQP9 in porcine liver is not of major physiological relevance.…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…This idea agrees with the functional and regulatory distinctions known to exist between AQP8 and AQP9 in rat liver (Garcia et al 2001, Kuriyama et al 2002. The absence of T3 regulation of AQP9 in rat liver does not confirm the increase in the mRNA levels of AQP9 seen by Caperna et al (2007) who looked at the expression and distribution of AQP9 in pig liver tissues after stimulation with hormones, such as glucagon, insulin, and T3. Because the T3-induced enhancement of AQP9 transcript seen by Caperna et al (2007) was not accompanied by a parallel increase in the same AQP at a protein level, it is conceivable to speculate that the T3 modulation of AQP9 in porcine liver is not of major physiological relevance.…”
Section: Discussionsupporting
confidence: 73%
“…These data suggest a negative effect exerted by T3 on the expression of the AQP8 gene. Unlike AQP8 in this study and AQP9 in a recent work using porcine liver (Caperna et al 2007), no significant changes were found at the mRNA level for AQP9, the other major AQP expressed in the rat liver, throughout the various thyroid states (data not shown).…”
Section: Effect Of T3 On the Transcription Of Liver Aqp8mentioning
confidence: 40%
See 2 more Smart Citations
“…There is growing interest in porcine hepatocyte models for use in the investigation of swine metabolic processes [1][2][3][4], as well as, in human clinical applications for transplantation/artificial liver support [5] or toxicological analyses [6]. In all cases, whether fresh ଝ Mention of trade name, proprietary product or vendor does not constitute a guarantee or warranty of the product by the U.S. Department of Agriculture or imply its approval to the exclusion of other products or vendors that may also be suitable.…”
Section: Introductionmentioning
confidence: 99%